The effect of physical preparedness levels on serum levels of CC16, SP-D and lung function in endurance runners - Pourmanaf, H.; Hamzehzadeh, A.; Nikniaz, L. (Science & Sports, 2020)
Objectives: Endurance runners are exposed to respiratory damages due to extreme endurance exercises. Increasing CC16 and SP-D in the bloodstream is a sign of respiratory tract damage. The purpose of this pilot study was to investigate the effect of physical preparedness levels on serum CC16 and SP-D levels and lung function.